Communicating at work : principles and practices for business and the professions - Adler, Ronald B. (Ronald Brian), 1946-; Elmhorst, Jeanne Marquardt (New York : McGraw-Hill, 2010)
Communicating at Work takes a pragmatic approach that features a strong multicultural focus, a heavy emphasis on effective presentations, and a pedagogical program designed to encourage group activities and skill building. This work provides coverage of new pedagogy, key new topics and an expansion of other important concepts including sources of on-the-job conflict, how to use informational interviews for career advancement, and stages in group problem-solving. --from publisher description
Communicating at work -- Communication, culture, and work -- Listening -- Verbal and nonverbal messages -- Interpersonal skills -- Principles of interviewing -- Types of interviews -- Working in teams -- Effective meetings -- Developing and organizing the presentation -- Verbal and visual support in presentations -- Delivering the presentation -- Types of business presentations.
Includes bibliographical references and index.
Keywords: Business communication; Interpersonal communication